The effect of temperature solubility on particle size and antibacterial activity of nanosilver of gembili’s inulin - Dian Eka Ermawati; Hayunda I'zaaz Fajrin; Sholichah Rohmani; M. Nur Dewi Kartikasari (Universitas Ahmad Dahlan, 2023)
Gembili Tuber (Dioscorea esculenta L.) is an Indonesia local tuber that reported to have potential as a source of inulin. Inulin is one of fiber types and carbohydrates sources derived from plants and has prebiotic and antibacterial activity. However, inulin long chain has low solubility in water, so it is necessary to modify the solubility in the biosynthetic process. In this study, the biosynthetic process was carried out using inulin as bioreducer of silver ions to help increase the absorption of gembili inulin. Gembili inulin was mixed with silver nitrat solution at variation temperature at 25 â„ƒ and 60 â„ƒ of biosynthetic process, in order to produce the expected particle size and antibacterial activity against bacteria Staphylococcus aureus and Eshcerichia coli. The results of this study indicate that variations in solubility temperature of inulin in nanosilver biosynthetic produce particle size of 12-49 nm with round shape. Whereas the temperature of inulin solubility did not show any significant difference towards AgNO3 control in the antibacterial activity test against S.aureus and E.coli bacteria. FTIR spectra showed that interaction between functional groups of silver nitrate and gembili inulin. Inulin only acts as a capping agent of nanosilver biosynthetic and does not induce antibacterial activity of nanosilver.